Tributação e direcionamento de mercado: como conjugar tributos, intervenção na economia e legitimidade? - Junqueira, Paula Moreira de Souza Lima (2017)
The essay is about Regulatory Law, specifically Tax Law, with important support from AdministrativeLaw. The objetive of the research is to answer to the question of which foundation of legitimacy thedecisions to intervene in the economy with taxes must own to be considered valids. The method ofresearch is bibliographic search with the intention to ground the theoretical conflict presented. Thestudy is initiated with Administrative Law to determine how the State can take decision in adetachment mode. In the second chapter, themes from Tax Law are explored to define how taxes canbe used to intervene in the economy and to induce behaviors and its requirements. The third chapter isdedicated to effectively answer the principal question of research by revealing the grounds thatdecisions of indirect intervention in the economy must have. In conclusion, the essay understands thatthe decision of using inductive taxation to intervene in the economy must be based fundamentally inprinciples, which is the nature of the rights and guarantees predicted in the Federal BrazilianConstitution of 1988.